Analysis of Public Satisfaction with the JKN Mobile Application in Samarinda City Using the SERVQUAL Method and the Customer Satisfaction Index - Muhammad Fadhilah; Heny Pratiwi; Ahmad Fahrijal Pukeng (Politeknik Pertanian Negeri Samarinda, 2026)
The rapid development of information and communication technology has significantly transformed the delivery of public services, particularly in the healthcare sector. One of the digital innovations introduced to improve healthcare accessibility in Indonesia is the JKN Mobile application developed by BPJS Kesehatan. This application enables participants to access various administrative services, membership information, healthcare facilities, and queue management systems online. As the number of users continues to increase, evaluating service quality becomes essential to ensure that the application meets user expectations and delivers satisfactory performance. This study aims to analyze public satisfaction with the JKN Mobile application in Samarinda City by integrating the Service Quality (Servqual) method and the Customer Satisfaction Index (CSI). Data was collected through a structured questionnaire distributed to active users of the JKN Mobile application, covering five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. The Servqual method was applied to measure the gap between users’ expectations and perceived performance, while the CSI method was utilized to determine the overall satisfaction level in the form of an index value. The results indicate that negative gaps are primarily found in the reliability and responsiveness dimensions, suggesting that system stability, transaction accuracy, and response time require improvement. In contrast, tangibles, assurance, and empathy dimensions demonstrate relatively positive evaluations. The overall CSI score categorizes user satisfaction as satisfied, although continuous service enhancement remains necessary. The integration of Servqual and CSI provides a comprehensive framework for identifying service weaknesses and supporting strategic improvements in digital healthcare services in Samarinda City.